A política de atração de investimentos industriais do Ceará e o impacto no emprego no período 2002-2005 - Nogueira, Fernando Antonio Nunes (2008)
This study aims to empirically assess the effectiveness of the Fund for Industrial Development (FDI) in the generation of employment, including the period from 2002 to 2005. Through the database of information from companies that received tax incentives to install, upgrade or relocate their investments in the State, were estimated two models: the first uses information cross-section and aims to raise the rate of employment growth formal. The other, using panel data, to investigate the effect of GDP per capita, the stock of human capital and consumption of electric power on the stock of formal jobs With regard to results, we can infer that the FDI was ineffective on its goal of generating jobs, is seen that the impact on the stock or the rate of formal job growth was zero, so future policies for industrial development the state of Ceará can be corrected (or revised) on how to implement.